Thyroid Nodule Inspection as Consideration for Surgery - Yuliana Yuliana (Scientiae Educatia: Jurnal Pendidikan Sains, 2018)
Thyroid gland is essential in our body metabolism. Sometimes there are nodules on it, whether on palpation or unexpected finding from an ultrasound test. Based on thyroid function importance in metabolism, then not all thyroid nodule needs to be operated. This article aims to know thyroid nodule test for operation consideration. Total thyroidectomy patients need hormonal thyroid replacement in life. Voice hoarseness and calcium imbalance metabolism often occur post-thyroidectomy. Therefore, operation indication should be well determined by considering risks for every patient. We found that only aggressively grown nodule and cancer need to be operated as soon as possible. Otherwise, it should be observed routinely every 6 to 12 months.